PERAN TIME MANAGEMENT TERHADAP PERILAKU DAN PERSEPSI MAHASISWA DALAM ORGANISASI - Agnes Cornelia J Abi; Kimiaus Saadah (Universitas Trunojoyo Madura, 2018)
ABSTRACTThis scientific article aims to provide an overview of how much time management influences students 'behavior and perceptions when they are members of the Student Activity Unit (UKM) at the Trunojoyo Madura University (UTM) and also analyzes the factors that influence students' perceptions of being a member of UKM. Time management is important to be studied by members of SMEs in order to improve the quality of human resources (HR) and organizational quality, in addition to this student perception is also useful to anticipate the cessation of SME members, the data collection method used in writing this article is collecting questionnaire data , for students who are still active as members of SMEs and students who are not active or stop being members of SMEs, the results obtained in the discussion of this article are time management, perception and interest greatly influence the activeness of students to become members of the organization